Nine shiny objects : a novel - Castleberry, Brian (Custom House, 2020)
June 26, 1947. Headlines across America report that an aviator from Idaho witnessed nine pulsating lights flying over the Cascade Mountains at speeds surpassing any aircraft built by humankind. Days later, a desperate Chicago pool hustler, inspired by the news, hitchhikes west in a fever-dream search for a possible extraterrestrial sign. A chance incounter with Saul Penrod, an Idaho farmer, and his family sets in motion the birth of "The Seekers"--a collective of outcasts, interlopers, and idealists devoted to creating a society where divisions of race, ethnicity, and sexuality are a thing of the past. Believing in their utopia, The Seekers attempt to settle in a community of their own creation. But one night their purpose is revealed in the wake of a horrific crime. In the decades that follow, the perpetrators, survivors, and their children will be forced to face the consequences of what happened.